2009
DOI: 10.1111/j.1462-2920.2008.01840.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cellulose production in Escherichia coli Nissle 1917 and its biological consequences

Abstract: Bacterial species of the Enterobacteriaceae family produce cellulose and curli fimbriae as extracellular matrix components, and their synthesis is positively regulated by the transcriptional activator CsgD. In this group of bacteria, cellulose biosynthesis is commonly regulated by CsgD via the GGDEF domain protein AdrA, a diguanylate cyclase that produces cyclic-diguanylic acid (c-di-GMP), an allosteric activator of cellulose synthase. In the probiotic Escherichia coli strain Nissle 1917 and its recent clonal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 43 publications
6
66
0
1
Order By: Relevance
“…It has been reported that calcofluor white binds to cellulose (for example: E. coli exopolysaccharide) (Brandl et al, 2011;Serra et al, 2013). Therefore fluorescence colonies on calcofluor agar denoted the bacterial cellulose production as some authors have described (Monteiro et al, 2009;Zogaj et al, 2001). In this work, biofilm of E. coli in the gas-liquid interface and botton from test tubes was observed as it described in other bacteria (Spiers et al, 2003) (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…It has been reported that calcofluor white binds to cellulose (for example: E. coli exopolysaccharide) (Brandl et al, 2011;Serra et al, 2013). Therefore fluorescence colonies on calcofluor agar denoted the bacterial cellulose production as some authors have described (Monteiro et al, 2009;Zogaj et al, 2001). In this work, biofilm of E. coli in the gas-liquid interface and botton from test tubes was observed as it described in other bacteria (Spiers et al, 2003) (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…Colonies that produce only curli fimbriae will lack the rugose characteristic but will still be deep red and slightly rough. Expression of cellulose only results in a rugose colony that is pink instead of deep red, and loss of expression of both products results in a colony that is white and smooth (29,50). Wild-type CFT073 and the yfiRNB locus mutants were grown for 6 days in LB at 37°C without shaking before serial dilution and plating on LB Congo red plates.…”
Section: Resultsmentioning
confidence: 99%
“…The capacity for cellulose biosynthesis is present in many bacteria from diverse branches of the phylogenetic tree, such as Thermotogae, Proteobacteria, and Cyanobacteria (246). Cellulose is a common component of environmental bacterial biofilms (247-250) and a component of interkingdom biofilms, i.e., bacteria attached to plants, fungi, and human intestinal cells (251)(252)(253)(254). One may recall that cellulose biosynthesis in the fruit-rotting bacterium G. xylinus was the first process shown to be regulated by c-di-GMP (1).…”
Section: Regulation Of Biofilmsmentioning
confidence: 99%
“…Indeed, c-di-GMP binds to the PilZ domain of the G. xylinus cellulose synthase (52), and in vitro cellulose biosyntheses using membrane fractions of G. xylinus and E. coli require only the substrate, UDP-glucose, c-di-GMP, and no other cytoplasmic components (1,253). Since the cellulose biosynthesis operon is expressed constitutively in G. xylinus, E. coli, and S. enterica (250,255,256), this posttranslational regulation is possibly the major mechanism of cellulose biosynthesis activation in these organisms.…”
Section: Regulation Of Biofilmsmentioning
confidence: 99%